Direct Instruction Learning Model to Improve Skills in Making Variant-Stuffed Layer Cake for Students with Hearing Impairment - Dona, Prima (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
This research have as a purpose to increase skill of deaf children in SLB Luak Nan Bungsu Payakumbuh to make layer cake with content variation. Problem happend in learning procces is all of learning, teacher teach the students with write in the white board, without demonstration learning by teacher in this learning processÂ  to make layer cake with fill in variation, so that ability of children to skilled to make layer cake with fill in variation. Based on the problem this research to prove that direct intruction learning can increase skill to make layer cake with fill in variation for deaf children. type of this research is classroom action research. Result of this research prove that direct instruction learning can increase skill to make layer cake with fill in variation for deaf children in SLB luak nan bungsu payakumbuh.